The Scottie barked at midnight - Dunnett, Kaitlyn (Dunnett, Kaitlyn. Liss MacCrimmon mystery., 2015)
Spring is just a few weeks away, but winter is still digging its claws into Moosetookalook, Maine. With business at the Scottish Emporium frozen up, Liss MacCrimmon is cautiously optimistic when a twist of fate lands her on a reality competition show - until the contest gets a little too cutthroat . . .While driving on an icy road one night, Liss swerves her car when something darts out in front of it. The Scottish terrier she finds shivering in the snow turns out to be a reality TV star. But when the pooch's owner is murdered, her daughter asks Liss to take her place on the reality show. Before Liss can tell her she's barking up the wrong tree, she finds herself ensnarled in the strange world of reality competitions and hot on the trail of a deadly competitor. And just as she starts pawing at the truth, Liss realizes she could be next on the murderer's list . . .